Lipid droplets, the Holy Grail of hepatic stellate cells: In health and hepatic fibrosis. Issue 5 (14th December 2022) - Mak, Ki M.; Wu, Catherine; Cheng, Christopher P.
Abstract: Lipid droplets (LDs) are distinct morphological markers of hepatic stellate cells (HSCs). They are composed of a core of predominantly retinyl esters and triacylglycerols surrounded by a phospholipid layer; the latter harbors perilipins 2, 3, and 5, which help control LD lipolysis. Electron microscopy distinguishes between Types I and II LDs. Type I LDs are surrounded by acid phosphatase‐positive lysosomes, which likely digest LDs. LD count and retinoid concentration are modulated by vitamin A intake. Alcohol consumption depletes hepatic retinoids and HSC LDs, with concomitant transformation of HSCs to fibrogenic myofibroblast‐like cells. LD loss and accompanying HSC activation occur in HSC cell culture models. Loss of LDs is a consequence of and not a prerequisite for HSC activation. LDs are endowed with enzymes for synthesizing retinyl esters and triacylglycerols as well as neutral lipases and lysosomal acid lipase for breaking down LDs. HSCs have two distinct metabolic LD pools: an "original" pool in quiescent HSCs and a "new" pool emerging in HSC activation; this two‐pool model provides a platform for analyzing LD dynamics in HSC activation. Besides lipolysis, LDs are degraded by lipophagy; however, the coordination between and relative contributions of these two pathways to LD removal are unclear. While induction of autophagy accelerates LD loss in quiescent HSCs and promotes HSC activation, blocking autophagy impairs LD degradation and inhibits HSC activation and fibrosis. This article is a critique of five decades of investigations into the morphology, molecular structure, synthesis, and degradation of LDs associated with HSC activation and fibrosis.